Air Temperature Fluctuations in Sarajevo and Climate Projections in the Context of Climate Change - Hrelja, Edin; Drešković, Nusret (Geographica Pannonica, 2026)
When discussing climate change, we primarily refer to global warming, that is, the in-crease in air temperature which directly affects other climatic elements. The Sarajevo meteorological station has a homogeneous series of observations and measurements of this climatic element spanning 136 years (from 1888 to 2024) without interruption, which represents a highly representative period for monitoring changes in air temperature and its fluctuations in the study area. The main characteristic of the thermal regime in the Sarajevo area is warming. The mean annual temperature for the entire instrumental period is 9.8°C, with a linear warming trend of 1.7°C. In addition to the general analysis of air temperature and its fluctuations in Sarajevo over this long-term observational period, special attention will be devoted to projecting this climatic element up to the year 2100 under different climate scenarios.
Keywords: climate change; air temperature; climate scenarios; Sarajevo